The nurse's role in promoting weight loss and encouraging healthier lifestyles. - Jebb, S; Sritharan, N (2005)
The increasing incidence of obesity in the UK has prompted a range of initiatives to raise awareness of the problem. In view of the well-known links between obesity and chronic disease, the focus is now on addressing the issue as part of patient care by advising adults and children on weight management and changes in diet and exercise.